Alternative pathways to climate change adaptation and disaster risk reduction mainstreaming and integration in development planning and budgeting of local government units - Magalang, Miguel; Jo, Arvin; La Vina, Antonio (Marinduque Council for Environmental Concerns (MACEC) ... [et al.], 2012)
This toolkit is an output of the Adaptation Knowledge Platform?s (AKP) capacity building activities in the Philippines. AKP and its country partner, the Ateneo School of Government (ASoG), facilitated a knowledge building process to enable them to: (1) raise the level of awareness of, and sharpen approaches to climate change adaptation (CCA); and (2) adopt a more transdisciplinary approach in crafting local development plans of the Albay and Iloilo provinces in the Philippines. As part of the process, AKP and ASoG carried out a series of learning dialogues in May 2012. This comprehensive toolkit incorporates findings from these dialogues and presents practitioners a twelve-step process guide to mainstreaming CCA and DRR into development planning.